PECULIARITIES OF LOVE MANIFESTATION IN PERSONALITIES WITH DIFFERENT TYPES OF STRESSES - Chkhaidze, Ann; Tsilinko, Irina (PSYCHOLOGICAL JOURNAL, 2019)
The article is devoted to theoretical analysis and empirical study of the specificity of love manifestation in individuals with different types of stresses. Theoretical information of the concepts “love”, “character”, “accentuation of personality traits” and the influence of character on the person are analyzed in this article. We distinguish six different styles of love relationships according to a study of the model of “love styles” by Canadian psychologist and sociologist J. A. Lee. Each style corresponds to a certain system of feelings and arrangements: eros – it is a passionate physical love, where a partner’s appearance is important and relationships develop very quickly. Storge – the passion grows slowly out of affection and friendship, it is based on similar interests. Mania - painful passion that is often accompanied by affective flashes, jealousy and even a feeling of hatred for your loved one. Lovers of this sort hesitate between passion and despair. This love corresponds to our cultural stereotype of “romantic love”. Agape - altruistic, “sacrificial” love, self-giving love. Such lovers think not about themselves, but about partners and what they can do for them. There is more spirituality than physical desire in this type of relationship. Pragma - prudent, calm feeling, where common sense prevails. Pragmatic lovers know what they want from a relationship, and set conditions that must be respected. Ludus – this style is used by those who see love as a game, it’s often not serious. Ludus lovers do not want to hurt, however, still often insult a partner. Sometimes this type of love implies relationships with numerous partners and is rarely accompanied by true deep feelings. According to A. N. Domracheva, the stress is a fundamental aspect in the formation of a growing personality, it determines socially significant behavior and activities. Types of character stresses, interpersonal relationships and styles of love in modern student youth were the subject of empirical analysis. We reviewed and analyzed the results of the correlation relationship between the types of character stresses and types of interpersonal communication with styles of love and it was found that these phenomena are closely related. A stress is the basis of personal development and is a driving aspect in its formation. It affects the formation of human behavior. The style of love is directly related to the character of the person. Person’s character traits, the choice of the type of interpersonal communication can play a major role not only in choosing a partner, but also in interpersonal interaction between lovers.